Program Daur Ulang Sampah Plastik Menjadi Ekobric (Daur Ulang Botol Bekas Sebagai Kreasi Tempat Pensil di MI Khodijah) - Biki Chusnun Najicha; Fadhil Akbar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Recycling waste is reprocessing unused goods into more useful goods and can have high economic value with. This research aims to see how people's efforts in maintaining the sustainability of nature and how the process of economic empowerment of the community through recycling itself. The purpose of this research also instills the soul of responsibility to always maintain the environment to mi Kodijah students. The result of this study is that there is awareness of students to always maintain the environment and awareness that the importance of recycling plastic waste. Students can also bring out their own creativity through recycling plastic waste. Plastic bottle waste recycling training activities are very beneficial for MI Khodijah students. This activity also provides additional knowledge and knowledge for MI Khodijah students on how to recycle plastic waste well.